Three-year summary-level of winter supplementation for steer calves both winter and summer grazed on bluestem pastures. - Smith, E.F.; Cox, R.F.; Koch, B.A.; Baker, F.H. (Kansas Agricultural Experiment Station, 2011)
The primary object of this test was to find the most desirable level of protein supplementation for wintering steer calves on dry bluestem pasture that are to be sold off summer grass as stocker or feeder yearlings.
Keywords: Beef; Bluestem pasture; Supplemental feed